Numerical simulation of drop impact and jet buckling problems using the eXtended Pom-Pom model - Oishi, C. M. [UNESP]; Martins, F. P. [UNESP]; Tome, M. F.; Alves, M. A. (Elsevier B.V., 2012)
This work presents numerical simulations of two fluid flow problems involving moving free surfaces: the impacting drop and fluid jet buckling. The viscoelastic model used in these simulations is the eXtended Pom-Pom (XPP) model. To validate the code, numerical predictions of the drop impact problem for Newtonian and Oldroyd-B fluids are presented and compared with other methods. In particular, a benchmark on numerical simulations for a XPP drop impacting on a rigid plate is performed for a wide range of the relevant parameters. Finally, to provide an additional application of free surface flows of XPP fluids, the viscous jet buckling problem is simulated and discussed. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Finite difference method; Free surface flows; Implicit techniques; Viscoelastic fluids; Drop impact; Jet buckling